José Agustín de la Puente Candamo, El Perú y su Independencia. Reflexiones ante el Bicentenario, Lima, Editorial Universitaria de la Universidad Ricardo Palma, 2021, 249 pp. - Jiménez López, José Gabriel (2022)
Fil: Jiménez López, José Gabriel. Universidad de Granada; España